2010
DOI: 10.1021/jm9017916
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis andin VitroBiological Evaluation of Carbonyl Group-Containing Inhibitors of Vesicular Acetylcholine Transporter

Abstract: To identify selective high-affinity inhibitors of the vesicular acetylcholine transporter (VAChT), we have interposed a carbonyl group between the phenyl and piperidyl groups of the prototypical VAChT ligand vesamicol, and its more potent analogues benzovesamicol and 5-aminobenzovesamicol. Of 33 compounds synthesized and tested, six display very high affinity for VAChT (Ki, 0.25 – 0.66 nM) and greater than 500-fold selectivity for VAChT over σ1 and σ2 receptors. Twelve compounds have high affinity (Ki, 1.0–10 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
45
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 28 publications
(46 citation statements)
references
References 56 publications
1
45
0
Order By: Relevance
“…[35-40] Evaluation of these 11 C- and 18 F-labeled radiotracers in rodents and microPET imaging studies in NHPs suggested that the radiolabeled version of several ligands ( 7-10, Figure 1 ) bound in vivo to the VAChT enriched striatal regions. [38-41] The half-life of 18 F (T 1/2 = 109.8 min) permits longer scan sessions that generate higher target-to-reference ratios; 18 F PET tracers also place fewer time constraints on tracer production.…”
Section: Introductionmentioning
confidence: 99%
“…[35-40] Evaluation of these 11 C- and 18 F-labeled radiotracers in rodents and microPET imaging studies in NHPs suggested that the radiolabeled version of several ligands ( 7-10, Figure 1 ) bound in vivo to the VAChT enriched striatal regions. [38-41] The half-life of 18 F (T 1/2 = 109.8 min) permits longer scan sessions that generate higher target-to-reference ratios; 18 F PET tracers also place fewer time constraints on tracer production.…”
Section: Introductionmentioning
confidence: 99%
“…Despite a slow brain kinetic, [ 18 F]FEOBV is the only PET tracer approved for imaging VAChT in human brains (Giboureau et al, 2007; Kilbourn et al, 2009; Petrou et al, 2014). Recently, our group designed a new class of VAChT inhibitors including (-)- TZ659 , which contain a carbonyl group attached to the 4-position of the piperidine ring (Efange et al, 2010; Li et al, 2013; Tu et al, 2009; Tu et al, 2012). (-)- TZ659 has a high affinity for VAChT, and a high selectivity for VAChT over σ 1 and σ 2 receptors; (-)-[ 11 C] TZ659 was successfully radiolabeled and showed a higher accumulation in the striatum of rats and nonhuman primates than in other non-target brain regions (Li et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…1) containing a carbonyl group to the 4-position of the piperidine ring of vesamicol. In vitro and in vivo evaluation of these compounds have revealed that the modification of the vesamicol structure by introducing a carbonyl group in between the two rings of the 4-phenylpiperidinyl fragment in the vesamicol structure yields benzovesamicol analogues with not only an increased affinity for VAChT but also with high selectivity for VAChT versus r receptors (Efange et al, 2010;Junfeng et al, 2013;Zhude et al, 2009 (Shiba et al, 2002(Shiba et al, , 2003 Kawamura et al, 2006) (Fig. 1), with high affinity and selectivity towards VAChT with significant preclinical findings.…”
Section: Introductionmentioning
confidence: 99%